2017
DOI: 10.1530/joe-16-0551
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of androgen and administration of estrogen induce transdifferentiation of testis into ovary

Abstract: Induction of sex reversal of XY fish has been restricted to the sex undifferentiated period. In the present study, differentiated XY tilapia were treated with trilostane (TR), metopirone (MN) and glycyrrhetinic acid (GA) (inhibitor of 3β-HSD, Cyp11b2 and 11β-HSD, respectively) alone or in combination with 17β-estradiol (E2) from 30 to 90 dah (days after hatching). At 180 dah, E2 alone resulted in 8.3%, and TR, MN and GA alone resulted in no secondary sex reversal (SSR), whereas TR + E2, MN + E2 and GA + E2 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 81 publications
1
9
0
Order By: Relevance
“…The downregulation of endogenous estrogen induces female trans-differentiation in juvenile and adult fish [17,28]. Impairing androgen synthesis and elevating exogenous estrogen can induce the male trans-differentiation in adult tilapia while exogenous estrogen alone can direct sex differentiation to female in juvenile fish [29]. These observations indicate the effects of sex hormone in the sex differentiation and maintenance in fish [30].…”
Section: Rationality Of Using Adult Sex Reversal Model To Study Earlymentioning
confidence: 87%
“…The downregulation of endogenous estrogen induces female trans-differentiation in juvenile and adult fish [17,28]. Impairing androgen synthesis and elevating exogenous estrogen can induce the male trans-differentiation in adult tilapia while exogenous estrogen alone can direct sex differentiation to female in juvenile fish [29]. These observations indicate the effects of sex hormone in the sex differentiation and maintenance in fish [30].…”
Section: Rationality Of Using Adult Sex Reversal Model To Study Earlymentioning
confidence: 87%
“…In mammals, the addition of estrogen could reverse the testis to the ovaries when blocking the expression of androgen. 21 Moreover, testosterone, as a hormone maintaining the male gonadal function, could improve the differentiation efficiency of insulin-producing cells from human induced pluripotent stem cells, regulate the adipose cell differentiation and promote proliferation and differentiation of rat myoblasts. [22][23][24] Additionally, the normal concentration of testosterone in human ranges from 14 to 25.4 nmol/L and different concentrations (10 −13 ∼ 10 −5 mol/L) of testosterone could induce 3T3-L1pre-adipocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently studies have revealed that sex hormones which could maintain gender and sexuality may accelerate the cell differentiation. In mammals, the addition of estrogen could reverse the testis to the ovaries when blocking the expression of androgen . Moreover, testosterone, as a hormone maintaining the male gonadal function, could improve the differentiation efficiency of insulin‐producing cells from human induced pluripotent stem cells, regulate the adipose cell differentiation and promote proliferation and differentiation of rat myoblasts .…”
Section: Discussionmentioning
confidence: 99%
“…Since male tilapia grow approximately twice as fast as females, a monosex population of sex-reversed males is commercially produced using androgen-supplemented feed. The mechanisms underlying sex differentiation and hormone-induced sex reversal of the gonads during early development have been well studied in tilapia 8 13 . However, the mechanisms underlying sex reversal in the tilapia brain remain unsolved.…”
Section: Introductionmentioning
confidence: 99%